2019
DOI: 10.1111/bjd.17583
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled proof‐of‐concept trial of digoxin and furosemide in adults with cutaneous warts

Abstract: SummaryBackgroundTopical ionic contraviral therapy (ICVT) with digoxin and furosemide inhibits the potassium influx on which DNA viruses rely for replication. Therefore, ICVT was hypothesized to be a potential novel treatment for cutaneous warts.ObjectivesTo assess the clinical efficacy, safety and tolerability of ICVT in adults with cutaneous warts. The secondary objective was to gain insight into the underlying working mechanism of ICVT.MethodsTreatment with ICVT was assessed for efficacy, safety and tolerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Indeed, topical and locally administered furosemide gel has demonstrated efficacy against warts caused by the human papillomavirus. 50 …”
Section: Antiviral Properties Of Furosemidementioning
confidence: 99%
“…Indeed, topical and locally administered furosemide gel has demonstrated efficacy against warts caused by the human papillomavirus. 50 …”
Section: Antiviral Properties Of Furosemidementioning
confidence: 99%
“…We previously showed that skin swabs can be used for antiviral treatment monitoring for cutaneous warts. 35,36 These studies showed a good correlation of the HPV load between swabs and gold standard biopsies. Performing swabs instead of multiple biopsies has major advantages: a lower patient burden because of its noninvasive nature, the ability to assess the viral load of a single lesion over time and its lack of curative effect, i.e.…”
Section: Discussionmentioning
confidence: 90%
“…This is the first study to show the use of skin swabs as a biomarker in the genital area related to antiviral treatment monitoring. We previously showed that skin swabs can be used for antiviral treatment monitoring for cutaneous warts . These studies showed a good correlation of the HPV load between swabs and gold standard biopsies.…”
Section: Discussionmentioning
confidence: 95%
“…The studies were approved by the Dutch Medical Ethics Committee (‘Stichting Beoordeling Ethiek Biomedisch Onderzoek’, Assen, the Netherlands). The clinical efficacy and safety results of these studies have been or will be reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The clinical efficacy and safety results of these studies have been or will be reported elsewhere. [18][19][20][21]…”
Section: Subjects and Designmentioning
confidence: 99%